Revealing The Advantages of the Best Cooking Oil Brand: A Case Study of Weighted Aggregated Sum Assessment (WASPAS) Method in Decision Support System - Hendriyani, Yeka; Mariani, Mariani; Rahmatika, Hayati; Emelsy, Nalurry (Jurnal Teknologi Informasi dan Pendidikan, 2023)
The purpose of this research is to implement the Weighted Aggregated Sum Product Assessment (WASPAS) method in determining the best cooking oil brand. The research method used is the Weighted Aggregated Sum Product Assessment (WASPAS) method with the stages of determining criteria, weights, and alternatives, creating a decision matrix, calculating the normalization value of the matrix and WASPAS weights in decision making Calculating the Qi value of normalization and weights makes ranking from the highest Qi value. From the research it is known that alternative A4 with the description Bimoli has the highest Qi value of 0.9162, so it is concluded that alternative A4 or Bimoli was chosen as the best cooking oil among the eight alternatives or other cooking oil brands. The result of this study is that the WASPAS method is able to recommend the selection of the best cooking oil for consumers.